Comparative evaluation of the potential anti-spasmodic activity of Piper longum, Piper nigrum, Terminalia bellerica, Terminalia chebula, and Zingiber officinale in experimental animals - Bansilal R. Tiwari; Mohammed Naseeruddin Inamdar; Raha Orfali; Ahmed Alshehri; Adel Alghamdi; Moneer E. Almadani; Sultan Alshehri; Syed Imam Rabbani; Syed Mohammed Basheeruddin Asdaq (Elsevier, 2023)
Background: Spasm of muscle is one of the frequent complaints seen by most of the population worldwide. The present study evaluated the efficacy of some of the commonly used herbal extracts against known spasmogens, such as histamine and 5-hydroxytryptamine (5-HT). Material and methods: The study was conducted on isolated guinea pig ileum and rat uterus preparations using histamine and 5-HT, respectively. Five herbal extracts such as Piper longum (P.L), Piper nigrum (P.N), Terminalia bellerica (T.B), Terminalia chebula (T.C), and Zingiber officinale (Z.O) were tested. Herbal extracts at doses 50, 150, 500, 1500, and 5000 mcg/ml were pretreated to the isolated tissue preparation, and the contractile response of histamine and 5-HT was recorded. The efficacy and the inhibitory concentration (IC50) were calculated and statistically analyzed by one-way ANOVA. Results: The study indicated that all five herbal extracts produced a concentration-dependent suppression of histamine and 5-HT-induced responses. A significant (p < 0.05) non-competitive antagonism was observed against the known spasmogen induced smooth muscle contraction for P.L, P.N, T.B, and Z.O in both guinea pigs and rat uterus preparation. Moreover, P.L and P.N completely abolished (100%) the contractile response induced by histamine and 5-HT. Although, T.C produced a concentration-dependent reduction in known spasmogen-induced contraction but the response was found to be statistically non-significant (p greater than 0.05). Conclusion: The finding suggested that P.L. and P.N. have better activity in terms of reducing the spasmogenic contractions compared to other extracts. Additionally, T.B. and Z.O. can lessen the uterine and intestinal contractions brought on by spasmogens. Although P.L and P.N demonstrated better efficacy against the spasmogenic activity of histamine and 5-HT, more research, particularly on isolated phytochemicals of the extracts and involving different experimental models, is required before establishing the precise safety and efficacy against spasmogenic-induced disorders.